Ethanol-Induced Death of Postnatal Hippocampal Neurons - Krista L. Moulder; Tao Fu; Heidi Melbostad; Robert J. Cormier; Keith E. Isenberg; Charles F. Zorumski; Steven Mennerick (Neurobiology of Disease, 2002)
Fetal alcohol exposure causes severe neuropsychiatric problems, but mechanisms of the ethanol-associated changes in central nervous system development are unclear. In vivo, ethanol's interaction with N-methyl-d-aspartate (NMDA) and γ-aminobutyric acid type A (GABAA) receptors may cause increased apoptosis in the immature forebrain. We examined whether ethanol affects survival of neonatal hippocampal neurons in primary cultures. A 6-day ethanol exposure killed hippocampal neurons with an LD50 of ∼25 mM. Elevated extracellular potassium or insulin-related growth factor 1 inhibited cell loss. Although potentiation of GABAA receptors or complete block of NMDA receptors also kills hippocampal neurons, pharmacological studies suggest that ethanol's interaction with GABAA and NMDA receptors is not sufficient to explain ethanol's effects on neuronal survival. Ca2+ influx in response to depolarization was depressed >50% by chronic ethanol treatment. We suggest that chronic ethanol may promote neuronal loss through a mechanism affecting Ca2+ influx in addition to effects on postsynaptic GABA and glutamate receptors.